Elements of the Habitus of Chinese Football Hooli-Fans and Countermeasures to Address Inappropriate Behaviour. (1st June 2020) - Hu, Jiahao; Cui, Guangying
Abstract: This paper relates to the spectator violence associated with men's football in China Following Pierre Bourdieu's Field Theory, the Chinese football 'field' can be understood as a social space where hooli-fans behaviour reflects aspects of a specific habitus, and it is this concept which represents the key focus of this study. In the empirical research on habitus reported here, 400 participants took part in a questionnaire survey. The data were subjected to Exploratory Factor Analysis in which four cultural factors were extracted, namely 1) a predisposition to promote barbaric behaviour, 2) attitudes to the concept of victory-defeat, 3) national self-esteem and 4) emotional abreaction. These four factors help to explain features of the aggressive behaviour of Chinese football hooli-fans. Additionally, these insights into the phenomenon of violence and aggression on the part of spectators contribute to understanding of development of countermeasures against hooli-fans. The solutions lie not simply with the hooli-fans themselves, but may be aided by the actions of players, the media and football's management bodies.